2003
DOI: 10.1002/bjs.4131
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in patients with primary hyperparathyroidism before and after successful parathyroidectomy

Abstract: The finding of reduced regional cerebral blood flow in patients with primary hyperparathyroidism followed by significant improvement after operation might influence the case for surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Following parathyroidectomy, regional blood flow returned to normal in all but 1 patient. Furthermore, 8 patients had high depression scores (Montgomery and Asberg Depression Rating Scale) preoperatively, with improved scores in 6 of the 8 patients following surgery [30]. One potential caveat to this study is that most of the patients had classical symptoms, and no similar study to date has been undertaken addressing patients with pHPT who suffer few symptoms of the disease.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Following parathyroidectomy, regional blood flow returned to normal in all but 1 patient. Furthermore, 8 patients had high depression scores (Montgomery and Asberg Depression Rating Scale) preoperatively, with improved scores in 6 of the 8 patients following surgery [30]. One potential caveat to this study is that most of the patients had classical symptoms, and no similar study to date has been undertaken addressing patients with pHPT who suffer few symptoms of the disease.…”
mentioning
confidence: 92%
“…Although this study is mainly observational, calcium is involved in neurotransmitter synthesis/release, and lowered CSF monoamine metabolites have been associated with depressive symptoms [29]. A study investigating regional cerebral blood flow and metabolism found reduced values compared with normal subjects in 14 of 16 patients with pHPT [30]. Reduced blood flow has also been demonstrated in depression [31].…”
mentioning
confidence: 94%
“…8,10 Cerebral blood flow may also be an explanatory factor. Mjåland et al 23 showed with single-photon emission computerized tomography that cerebral blood flow was pathologically reduced in 14 of 16 females with pHPT preoperatively and normalized after parathyroidectomy in almost all cases (13/14).…”
Section: Commentmentioning
confidence: 99%
“…While this study is mainly observational, calcium is involved in neurotransmitter synthesis/release, and lowered CSF monoamine metabolites have been associated with depressive symptoms [29]. A study investigating regional cerebral blood flow and metabolism found reduced values compared to normal subjects in 14 of 16 patients with pHPT [30]. Reduced blood flow has also been demonstrated in depression [31].…”
Section: Neuropsychiatric Symptoms and Quality Of Lifementioning
confidence: 94%
“…Following parathyroidectomy, regional blood flow returned to normal in all but one patient. Furthermore, eight patients had high depression scores (Montgomery and Asberg Depression Rating Scale) preoperatively with improved scores in six of the eight patients following surgery [30]. One potential caveat is that most of the patients in this study had classical symptoms and no similar study to date has been undertaken addressing patients with pHPT that suffer with a mild form of the disease.…”
Section: Neuropsychiatric Symptoms and Quality Of Lifementioning
confidence: 94%